2009
DOI: 10.1007/s10853-009-3262-9
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic matrix composites containing carbon nanotubes

Abstract: Due to the remarkable physical and mechanical properties of individual, perfect carbon nanotubes (CNTs), they are considered to be one of the most promising new reinforcements for structural composites. Their impressive electrical and thermal properties also suggest opportunities for multifunctional applications. In the context of inorganic matrix composites, researchers have particularly focussed on CNTs as toughening elements to overcome the intrinsic brittleness of the ceramic or glass material. Although th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
214
1
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 364 publications
(227 citation statements)
references
References 145 publications
5
214
1
7
Order By: Relevance
“…As reported in a review paper by Cho et al [10] and observed in this work, the electrical conductivity of CNT loaded systems tends to be approximately one to two orders of magnitude higher than that of carbon black composites, due to the higher intrinsic conductivity of CNTs and the much higher connectivity of the network. In this context, the high axial electrical conductivity of CNT and GNP not only offers the potential for fabricating conducting ceramics but also responsive ceramic systems.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…As reported in a review paper by Cho et al [10] and observed in this work, the electrical conductivity of CNT loaded systems tends to be approximately one to two orders of magnitude higher than that of carbon black composites, due to the higher intrinsic conductivity of CNTs and the much higher connectivity of the network. In this context, the high axial electrical conductivity of CNT and GNP not only offers the potential for fabricating conducting ceramics but also responsive ceramic systems.…”
Section: Resultssupporting
confidence: 71%
“…Composite materials, filled with carbon nanofillers, are being researched for emerging applications like energy, transportation, defence, automotive, aerospace, sporting goods, and infrastructure sectors [9]. Particularly among ceramic based materials, CNTs have been reported to significantly improve mechanical, thermal and electrical properties of the ceramic nanocomposites [10]. For polymeric systems, carbon nanofillers have also proved to be very attractive because they offer structural damage sensing ability and the subject has been widely investigated [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Note that CNTs are characterized by similar superior values of strength and elastic moduli, as with pristine graphene [21][22][23]. With these remarkable mechanical characteristics of CNTs, ceramic-CNTs nanocomposites show excellent mechanical properties [21][22][23].…”
Section: Fracture Behaviour Of Ceramic-graphene Nanocompositesmentioning
confidence: 95%
“…reviews [21][22][23][24] and original research papers [5][6][7]12]). Such nanocomposites typically (but not always) contain carbon nanoinclusions at GBs (figure 2) [21][22][23][24][25].…”
Section: Specific Structural Features Of Nanoceramicsmentioning
confidence: 99%
See 1 more Smart Citation